Total synthesis of a reversed cyclopurpuracin using a combination of solid and solution phase methods. (27th July 2022) - Yayat, Hasna Noer Agus; Maharani, Rani; Hidayat, Ace Tatang; Wiani, Ika; Zainuddin, Achmad; Mayanti, Tri; Nurlelasari,; Harneti, Desi; Supratman, Unang
Abstract: Cyclopurpuracin is a cyclooctapeptide isolated from the methanol extract of Annona purpurea seeds with the following sequence cyclo‐Gly‐Phe‐Ile‐Gly‐Ser‐Pro‐Val‐Pro residue. In this study, a reversed cyclopurpuracin, namely cyclo‐Pro‐Val‐Pro‐Ser‐Gly‐Ile‐Phe‐Gly, was successfully synthesized using a combination of solid and solution phase synthesis methods. The precursor was head‐to‐tail cyclized using 1.25 mM in DCM with 3 eq. HBTU and 1% v/v DIPEA. The final product was obtained (3.8 mg) with an overall yield of 7.4%. The synthetic products were characterized by HR‐ToF‐MS, 1 H‐NMR, 13 C‐NMR, and 2D NMR, showing different NMR profiles. The presence of the conformation was confirmed by providing additional signals in the 1 H NMR and 13 C NMR spectrum and the correlation peaks shown by 2D NMR. The presence of the cis conformer in conformer B was proven by the chemical shifts of Ser 6 Cβ, Pro 7 Cβ, and Pro 8 Cβ in conformer B, which were more upfield than the conformer A chemical shifts, and the presence of NOE correlation between Hα/Hα of Val 7 and Pro 8 . The NMR of the reversed cyclopurpuracin revealed the presence of two conformers, conformer A (cyclo‐[ trans ‐Pro‐Val‐ trans ‐Pro‐Ser‐Gly‐Ile‐Phe‐Gly]) and conformer B (cyclo‐[ cis ‐Pro‐Val‐ trans ‐Pro‐Ser‐Gly‐Ile‐Phe‐Gly]). The presence of dual conformers has not been observed in the NMR spectra of natural cyclopurpuracin. Abstract : In this study, a reversed cyclopurpuracin, namely cyclo‐Pro‐Val‐Pro‐Ser‐Gly‐Ile‐Phe‐Gly, was successfully synthesized using a combination of solid and solution phase synthesis methods. The final product was obtained with an overall yield of 7.4% and the NMR revealed the presence of two conformers, conformer A (cyclo‐[ trans ‐Pro‐Val‐ trans ‐Pro‐Ser‐Gly‐Ile‐Phe‐Gly]) and conformer B (cyclo‐[ cis ‐Pro‐Val‐ trans ‐Pro‐Ser‐Gly‐Ile‐Phe‐Gly]).